The alliance between nerve fibers and stem cell populations in bone marrow: life partners in sickness and health. Issue 8 (24th April 2019) - Leitão, Luís; Alves, Cecília J.; Sousa, Daniela M.; Neto, Estrela; Conceição, Francisco; Lamghari, Meriem
ABSTRACT: The bone marrow (BM) is the central hematopoietic organ in adult mammals, with great potential to be used as a tool to improve the efficacy of the body's response to a number of malignancies and stressful conditions. The nervous system emerges as a critical regulatory player of the BM both under homeostatic and pathologic settings, with essential roles in cellular anchorage and egress, stem cell differentiation, and endothelial cell permeability. This review collects the current knowledge on the interplay between the nervous system and the BM cell populations, with a focus on how the nervous system modulates hematopoietic stem and progenitor cell, mesenchymal stromal cell, and endothelial progenitor cell activity in BM. We have also highlighted the pathologies that have been associated with disturbances in the neuronal signaling in BM and discussed if targeting the nervous system, either by modulating the activity of specific neuronal circuits or by pharmacologically leveling the activity of sympathetic and sensorial signaling‐responsive cells in BM, is a promising therapeutic approach to tackling pathologies from BM origin.—Leitão, L., Alves, C. J., Sousa, D. M., Neto, E., Conceição, F., Lamghari, M. The alliance between nerve fibers and stem cell populations in bone marrow: life partners in sickness and health. FASEB J. 33, 8697–8710 (2019). www.fasebj.org